Tingkat Kepuasan Siswa terhadap Pelaksanaan Ekstrakurikuler Tari di SD Muhammadiyah Plus Salatiga - Mahmudatul Lathifa; Tegar Syifa’i Renjananta; Fi Wulan Aseh; Yogi Kuncoro Adi (LaKaspia, 2025)
This study was motivated by the importance of extracurricular activities in developing students’ potential, interests, and character, including dance activities that are popular among students. The study aimed to determine students’ satisfaction with the dance extracurricular program at SD Muhammadiyah Plus Salatiga. A survey method with a quantitative descriptive approach was employed over one month. Data were collected from 20 students participating in the dance extracurricular program using a questionnaire consisting of 15 indicators across three aspects: service quality, emotional satisfaction, and social satisfaction. The results indicated an overall satisfaction level in the Very Satisfied category (overall mean = 3.28). The mean scores for each aspect were 3.36 (service quality), 3.15 (emotional satisfaction), and 3.33 (social satisfaction), with responses predominantly falling into the Satisfied and Very Satisfied categories. Students’ satisfaction was reflected in effective time management, positive feelings during practice sessions, and cooperative and respectful peer interactions. Nevertheless, several indicators require improvement, including more adaptive program management through enhancing instructors’ competence, providing adequate spaces and facilities to support students’ potential development, and strengthening students’ discipline and responsibility to continuously improve satisfaction and learning experiences.